Concepção de um conversor DC-DC auto-oscilante aplicado a um sistema energy harvesting - Naidon, Thiago Cattani (2015)
This thesis aims to present the design and development of a self-oscillating DC-DC converter applied to an Energy Harvesting (EH) system. The relevance of this study is caracterized by the proposed standard analysis with the objective of defining the parameters of the design as well as providing a reduction in switching losses. The converter is designed to operate in Zero Voltage Switching (ZVS) and, thereby, to increase the efficiency and reduce the Electromagnetic Interference (EMI). The primary function of an EH system is to obtain, convert, condition and manage power from a source available in the environment. In general, this technique is used to power low power devices which usually would be powered by batteries. There are several energy sources that can be used to EH systems, however, this study focus on solar energy, for two main reasons: first, the output the panels is continuous voltage (DC) and also the high power density, which enables its use for a lot of applications. The proposed circuit is composed by a step-up self-oscillating converter, which start-up is promoted by an Greinacher multiplier voltage circuit, that acts as a auxiliary circuit. The output of the converter has a rectification stage. The circuit is capable of operating with starting voltage of at least 50 mV, and reaching output voltage values greater than 20V, with 10 mW of power. The experimental results and simulation are presented in order to demonstrate and validate the design, analysis performed with the DC-DC converter self-oscillating.